PENERAPAN MODEL KOOPERATIF TIPE STAD DALAM PEMBELAJARAN IPS TENTANG MASALAH SOSIAL KELAS IV SD - Dewa, Neno Firmansyah (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Abstract: Application of Model Cooperative STAD type in Social Sience Learning About Social Issues at four grade state elementary school. The purpose of this research were (1) describe application of cooperative STAD type in Social Sience Learning About Social Issues at four grade state elementary school, (2) describe constraints and solutions applicatian Model STAD Cooperative STAD type in Social Sience Learning About Social Issues at four grade state elementary school. This study is classroom action research (CAR) conducted in three cycles, each cycle consist of planning, action, observation, and reflection. The result showed that (1) The steps of learning cooperative STAD type are: a) preparation, b) Presentation of Class, c) Learning in Groups, d) Individual Test, e) Improved Individual Score, and f) Award. (2) the constraint of learning find in: a) preparation of learning, b) control of the class, c) giving attention, motivation and reward, d) time management, e) giving the question, f) the execution form of multiple choise evaluation. The solution were prepare again application steps of cooperative STAD type in learning process. Keywords: cooperative STAD type, learning, social sience Abstrak: Penerapan Model Kooperatif Tipe STAD dalam Pembelajaran IPS Tentang Masalah Sosial Kelas IV SD. Tujuan penelitian ini untuk (1) mendeskripsikan Penerapan Model Kooperatif Tipe STAD dalam Pembelajaran IPS Tentang Masalah Sosial Kelas IV SD, (2) mendeskripsikan kendala dan solusi dalam penerapan model kooperatif tipe STAD, pembelajaran IPS di kelas IV SD. Penelitian ini merupakan PTK terdiri dari tiga siklus, setiap siklus ada tiga pertemuan setiap pertemuan terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi.Hasil penelitian menunjukkan bahwa (1) langkah pembelajaran model kooperatif tipe STAD yaitu: a) Persiapan, b) Penyajian Kelas, c) Belajar dalam Kelompok d) Tes Indivi-du e) Peningkatan Skor Individu, dan f) Penghargaan. (2) Kendala yang ditemui yaitu pada langkah-langkah: a) persiapan pembelajaran, b) penguasaan kelas, c) pemberian perhatian, motivasi dan penghargaan, d) pengaturan waktu, e) pemberian pertanyaan, f) pengerjaan soal evaluasi bentuk subjektif. Solusinya adalah persiapkan kembali langkah-langkah penerapan model kooperatif tipe STAD dalam proses pembelajaran. Kata kunci: kooperatif tipe STAD, pembelajaran, IPS